Genetic characterization of clonal complex sequence type 2057 (cc2057) serogroup B Neisseria meningitidis strains unique to Japan and identification of a capsular-switched serogroup Y isolate cc2057. Issue 3 (3rd March 2022) - Takahashi, Hideyuki; Morita, Masatomo; Kamiya, Hajime; Nakamura-Miwa, Haruna; Shimuta, Ken; Ohnishi, Makoto
Abstract : Introduction. Only approximately 40 cases of invasive meningococcal diseases are reported annually in Japan, and the dominant strains are serogroup Y meningococci (MenY) followed by serogroup B meningococci (MenB). Within the last 10 years, Neisseria meningitidis strains belonging to clonal complex (cc)2057 have become dominant among Japanese MenB and have not been identified in countries other than Japan. Hypothesis/Gap Statement. The uniqueness of cc2057 N. meningitidis strains was considered to be epidemiologically of importance, and some genetic features could be hidden in the genome of cc2057 meningococci. Method. We investigated 22 cc2057 MenB and one cc2057 MenY using whole genome sequencing (WGS) and also predicted the potential coverage of 4CMenB and bivalent rLP2086 vaccines in silico . Results. cc2057 N. meningitidis strains were phylogenetically assigned to two clades. Three hypothetical genes homologous to those in Neisseria lactamica and sequences related to a new CRISPR Cas9 system were found only in the genome of cc2057 strains. Moreover, one cc2057 MenY strain was presumed to be capsular-switched at the capsule synthesis ( cps ) locus. The potential coverage of 4CMenB and rLP2086 for cc2057 MenB strains was estimated to be very low. Conclusion. To the best of our knowledge, this is the first study to provide genetic insights from epidemiologically unique N. meningitidis cc2057 strains isolated only in Japan, an island country.